Poly(ethylene glycol) Methacrylate/Dimethacrylate Hydrogels for Controlled Release of Hydrophobic Drugs - Diramio, Jackie A.; Kisaalita, William S.; Majetich, George F.; Shimkus, Joel M. (Biotechnology progress, 2005)
Hydrogels have been successfully used to entrap hydrophilic drugs and release them in a controlled fashion; however, the entrapment and release of hydrophobic drugs has not been well studied. We report on the release characteristics of a model hydrophobic drug, the steroid hormone estradiol, entrapped in low (MW 360/MW 550) and high (MW 526/MW 1000) molecular weight poly(ethylene glycol) methacrylate (PEG‐MA)/dimethacrylate (PEG‐DMA) hydrogels. The cross‐linking ratio, temperature, and pH ranged from 10:1 to 10:3, from 33 to 41 °C, and from 2 to 12, respectively. The gelation of the PEG‐MA/PEG‐DMA hydrogel was initiated with UV irradiation. The absence of poly(glutamic acid) in the hydrogel formulation resulted in a loss of pH sensitivity in the acidic range, which was displayed by the hydrogels' similarities in swelling ratios in the pH buffers of pH 2, 4, and 7. Use of high molecular weight polymers resulted in a higher hydrogel swelling (300%) in comparison to the low molecular weight polymers. Drug size was found to be a significant factor. In comparison to 100% estradiol (MW 272) release, the fractional release of insulin (MW 5733) was 12 and 24% in low and high molecular weight gels at pH 2, respectively, and 17% in low molecular weight gels at pH 7. On the release kinetics of the estradiol drug, the hydrogels displayed a non‐Fickian diffusion mechanism, which indicated that the media penetration rate is in the same range as the drug diffusion. The synthesis, entrapment, and release of estradiol by the PEG‐MA/PEG‐DMA hydrogels proved to be successful, but the use of ethanol in the buffers to promote the hydrophobic release of the estradiol in the in vitro environment caused complications, attributed to the process of transesterification.